Developing Public Speaking Ability For the Teachers of SMP Jamiah Al-Aziziyah Batee Iliek Samalanga - Nusir, Firman; Bahri, Saiful; Kasir, Ibnu (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Teachers are the backbone of an educational institution. The progress or setback of an educational institution is determined by the role of teachers. Through observations and interviews conducted with the Headmaster of SMP Jamiah Al-Aziziyah Batee Iliek, it was found that the majority of teachers lack proficient public speaking skills. Based on this issue, it is necessary to organize activities to enhance public speaking skills, which are crucial for the teachers of SMP Jamiah Al-Aziziyah Batee Iliek. The method of implementing these activities is through lecture-based methods. The stages of the activities include pre-implementation, implementation, and evaluation. Technically, a theoretical explanation related to public speaking skills is provided, and participants then engage in practical exercises. After the lectures, participants are assigned tasks and provided guidance to create speech scripts on themes relevant to the school's needs. The results of the community service activities aimed at enhancing public speaking skills have shown improvement among the participants. According to the participants' questionnaire responses, there was an increase in understanding the criteria for effective speakers, with 20% previously not understanding and 80% having an average level, which improved to 40% understanding and 60% having a high level of understanding. During the practical exercises, all participants successfully overcame confidence issues while speaking. The results of the task to compose speech scripts were quite satisfactory, with an average score of 77.5 out of 100.